MANAJEMEN PEMBELAJARAN MATEMATIKA MENGGUNAAN METODA AKTIF KREATIF DI SMK - Eka Agustina (UNIVERSITAS BENGKULU, 2016)
The research objective was to determine whether the management study of mathematics by applying the method of Creative Active can improve students' competence in Maths . This research was conducted in classes X SMK STATE 5 Bengkulu City. This research was conducted using the method of classroom action research that includes four components of action: planning, action, observation, reflection through several cycles . Data were collected through observation sheets and the results of the written evaluation . Based on the results of this study concluded that in every cycle there is a significant increase in the learning process in which the ke- I cycle around53.61 % in the 2nd cycle and 67.31 % in the 3rd cycle of 83.08 % . Then the activity of students in mathematics with an active creative method is very good .Keywords: management, learning, mathematic, creative active